Development of a novel switched packed bed process for cryogenic CO2 capture from natural gas - Babar, M. (Institution of Chemical Engineers, 2021)
Desublimation-based Carbon dioxide (CO2) removal from the natural gas (NG) in a cryogenic packed bed becomes challenging due to the dry ice formation inside the packed bed. Therefore, the cryogenic packed bed has been used for NG purification only in batch processes. However, to fulfill the energy requirements, it is crucial to develop a continuous process for NG purification, which is difficult for a single cryogenic packed bed. In the current research, a novel cryogenic packed bed system is proposed for continuous capture of desublimation based CO2 capture from natural gas. The process feasibility of the switching concept was proved through dynamic simulation and experimental study on CO2 separation from multi-component NG. It was observed that increasing CO2 content decreases the switching and saturation time of the cryogenic packed bed. The total energy required per packed bed per cycle in the switching system is 133.35. The saturation time for pure CO2 feed, NG sample-1, and NG sample-2 were 300, 500, and 600 s, respectively. An excellent agreement was observed between the results obtained from the experimental results and that obtained through dynamic simulation. A switching time of 200 s was found for a CO2 recovery of more than 98 . This research work offers scientific data and theoretical support for the industrial application of switched cryogenic packed bed setup in CO2 capture from natural gas in the future. Moreover, in the current research work, scale-up study, and automatic control system for the switched packed bed are recommended for the future. Â© 2021 Institution of Chemical Engineers